If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3y = 30 Solving 6x + -3y = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 6x + -3y + 3y = 30 + 3y Combine like terms: -3y + 3y = 0 6x + 0 = 30 + 3y 6x = 30 + 3y Divide each side by '6'. x = 5 + 0.5y Simplifying x = 5 + 0.5y
| 18x+10-14x=-34 | | 9x-7=28+4x | | m/4-4.6=-3.1 | | 18=r(2) | | X=5.6 | | 7(1)-8y=56 | | 5=4(3y-2) | | 11x-18=3+8x | | 6x+8x+10=66 | | 6-(3z-1)=6-4z | | 7x-8(0)=56 | | 6x+10=4x-8 | | r^2-15=-2r | | 9(y-6)=8(y-9) | | -1/2x^2+100x | | 7(0)-8y=56 | | 13x-12=49x+24 | | 24z-48z=.72 | | 5x-14=x-(24+4x) | | w-3/2=5/8 | | -11/2h=4 | | 4(x-4)+6=6x-2(3+x) | | x+(x-12)=58 | | -31/3b=5 | | 14x-8x+9=33 | | 14x-8+9=33 | | (1+3w)(2)= | | 9m+1/4=8/1/2m+2/3 | | 4x-5=4(x+7) | | 18x+12-14x=-24 | | x-0.25+25.00=250.00 | | 7/10m=10 |